IBM Pengendalian Hipertensi dengan Pemakaian Obat secara Rasional, Kontrol dan Olahraga Teratur di Desa Simirik Kecamatan Padangsidimpuan Batunadua Kota Padangsidimpuan - Daulay, Nanda Masraini; Hidayah, Arinil (Jurnal Pengabdian Masyarakat Aufa (JPMA), 2021)
The prevalence of hypertension has increased over the last few decades and has become a major health problem because awareness of treatment and the level of hypertension control are still very low (Li Y, Yang L et al, 2017). This educational activity aims to increase the knowledge of hypertension sufferers in controlling hypertension with rational use of drugs, control and regular exercise. The activities carried out consisted of measuring blood pressure, distributing knowledge questionnaires, and education about controlling hypertension. The number of participants was 25 people with hypertension. The results of this activity found 20 people (80%) with hypertension who understood hypertension control with good knowledge category. Meanwhile, 5 people (20%) did not understand hypertension control with the category of lack of knowledge. The average value of systolic blood pressure is 176 mmHg and the average value of diastolic blood pressure is 103 mmHg. The community seemed enthusiastic and able to mention hypertension control. PKM on hypertension control education with rational use of drugs, control and regular exercise can be carried out routinely with additional complementary therapies such as herbal therapy in lowering blood pressure.